Применение микроконтроллеров в IoT - Литвиненко, Т. В. (ХНУРЕ, 2020)
The aim of this work is the use of microcontrollers to create the Internet of things and the convenience of their use in the modern world.
Keywords: микроконтроллер; энергосбережение; ULPBench™; SimpleLink; технология энергосбережения